Awareness, knowledge, and factors that influenced the uptake of screening tests for prostate cancer among men aged 40 and older in Ido-Ekiti, Ekiti State, Nigeria - Kayode R. Adewoye; Shuaib K. Aremu; Waheed A. Adegbiji; Chijioke C. Achebe (AOSIS, 2023)
Background: Despite being the second most common and deadliest cancer in males, prostate cancer could go unnoticed in the early stages. Prevention programs have been set in place to help in the early detection and reduction of mortality rates in developed countries. Objective: The aim of this study was to determine awareness, knowledge, and the uptake of prostate cancer screening tests. Another objective was to identify the factors that determine the uptake of prostate cancer screening among men living in Ido-Ekiti. Methods: A cross-sectional study was conducted among males aged 40 and above living in Ido-Ekiti in Ido-Osi local government area, Ekiti State, Nigeria. The sample size of 380 respondents was obtained using Leslie Fisher's formula. Results: The study revealed that the majority of the correspondents are aware of prostate cancer (57.9%). More than two-thirds of the respondents have poor knowledge of prostate cancer and the screening test (74.4%), with a median knowledge score of 30%. The uptake of prostate cancer screening tests was very low among the respondents (18.2%). Conclusion: Despite the high level of awareness of prostate cancer disease among the respondents, the majority have poor knowledge of the disease and the screening test. There was a low uptake of prostate cancer screening tests among the respondents.